Guiding Documents for Engaging with Remote Chronic Disease Management Programs as a Healthcare Provider: A Scoping Review - Van Damme, Jill; Dal Bello-Haas, Vanina; Kuspinar, Ayse; Strachan, Patricia; Peters, Nicole; Nguyen, Khang Trong; Bolger, Greg (International Journal of Telerehabilitation, 2023)
Introduction: Chronic disease management programs (CDMP) that include education and exercise enhance outcomes and reduce healthcare costs. Remote CDMP have the potential to provide convenient, cost-effective, and accessible options for individuals, but it is unclear how to best implement programs that include education and exercise. This review identified and synthesized resources for implementing remote CDMP programs that incorporate education and exercise. Methods: Peer-reviewed and grey literature were systematically searched from January 1998 to May 2022. Covidence software was used for screening and extraction. The data were synthesized and presented in a narrative and tabular format. Results: Six peer-reviewed manuscripts and six grey literature documents published between 2006-2022 were included. All resources described individual programs targeting various chronic conditions. Provider training, consent, participant screening, and safety considerations were identified. Conclusions: Guidelines for remote CFMP programs are lacking. Additional work is needed to design remote CDMP guidelines incorporating education and exercise.